2013
DOI: 10.5336/medsci.2012-31986
|View full text |Cite
|
Sign up to set email alerts
|

The Predictability of Lymph Node Metastasis in Patients with Endometrial Cancer

Abstract: A AB BS ST TR RA AC CT T O Ob bj je ec ct ti iv ve e: : The aim of this study was to predict lymphatic involvement in endometrial cancer patients using clinicopathological variables in patients treated with surgical staging. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : A retrospective chart review was performed in 147 women with pathologically proven endometrial carcinoma (EC) who were treated between January 2006 and January 2011. Surgically staged 125 patients were included in this study. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…However, we did find that serum CA15-3 levels differed significantly according to tumor size, histological type (Type 2 > Type 1), histological grade (Grade 3 > Grade 1-2), and positive LVSI and LNI statuses. In previous studies, Scambia et al, 3 Li et al, 5 and Yildiz et al 19 reported significant associations between serum CA15-3 levels and FIGO stage, histological grade, and a positive LNI status. However, we demonstrate significant associations between serum CA15-3 levels and tumor size, histological type, and a positive LVSI status.…”
Section: Discussionmentioning
confidence: 91%
“…However, we did find that serum CA15-3 levels differed significantly according to tumor size, histological type (Type 2 > Type 1), histological grade (Grade 3 > Grade 1-2), and positive LVSI and LNI statuses. In previous studies, Scambia et al, 3 Li et al, 5 and Yildiz et al 19 reported significant associations between serum CA15-3 levels and FIGO stage, histological grade, and a positive LNI status. However, we demonstrate significant associations between serum CA15-3 levels and tumor size, histological type, and a positive LVSI status.…”
Section: Discussionmentioning
confidence: 91%